Some Examples from the History of the Formation of Eurasian Integration - A., Gonashvili; Mansurovich, Salixov Shoxrux (Researchparks Publishing, 2023)
The article presents historical information about the development and formation of Eurasian integration as a regional process in the post-Soviet space. The experience of the transformation of independent states in Eurasia shows that the speed of awareness of the new reality and the adaptation of actors to its requirements in different post-Soviet societies was different from each other. This situation contributes to the idea of the processes of social change taking place in the post-Soviet space as a kind of world laboratory, where different economic, socio-political, cultural and civilizational models are tested, taking into account not only domestic conditions, but also the international context. The problems faced by the states and societies of the Eurasian space are closely intertwined with the fundamental global changes taking place in the world today. The year 2019 marked the 25th anniversary of an important phenomenon in the socio-economic and political life of Eurasian content countries, namely the regional integration process dubbed